Genetic and Pharmacological Inhibition of GCN2 Ameliorates Hyperglycemia and Insulin Resistance in Type 2 Diabetic Mice - Juntao Yuan; Fang Li; Xiyue Shen; Junling Gao; Zhuoran Yu; Kai Luo; Bingqing Cui; Zhongbing Lu (MDPI AG, 2022)
It is well recognized that there is a strong and complex association between nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D). We previously demonstrated that genetic knockout or pharmacological inhibition of general control nondepressible kinase 2 (GCN2), a well-known amino acid sensor, alleviated hepatic steatosis and insulin resistance in obese mice. However, whether GCN2 affects the development of T2D remains unclear. After a high-fat diet (HFD) plus low-dose streptozotocin (STZ) treatments, Gcn2−/− mice developed less hyperglycemia, insulin resistance, hepatic steatosis, and oxidative stress than wild-type (WT) mice. Inhibition of GCN2 by intraperitoneal injection of 3 mg/kg GCN2iB (a specific inhibitor of GCN2) every other day for 6 weeks also ameliorated hyperglycemia, insulin resistance, hepatic steatosis, and oxidative stress in HFD/STZ- and leptin receptor deletion (db/db)-induced T2D mice. Moreover, depletion of hepatic GCN2 in db/db mice by tail vein injection of an AAV8-shGcn2 vector resulted in similar improvement in those metabolic disorders. The protective mechanism of GCN2 inhibition in T2D mice was associated with regulation of the glucose metabolic pathway, repression of lipogenesis genes, and activation of the Nrf2 pathway. Together, our data provide evidence that strategies to inhibit hepatic GCN2 activity may be novel approaches for T2D therapy.